Investigating the mechanism of action of hormones used in hormone replacement therapy via estrogen receptor subtypes and the influence of the progesterone receptor - Perkins, Meghan Samantha (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.